Evolution of Occupational Accident Rates by Geographic Zone in Ecuador, Period 2015-2021 - Espinoza-Guano, Mónica (2023)
The article explains as background that the management of Occupational Safety and Health is a challenge for organizations seeking to be more competitive by being recognized for their socially responsible approach, the professional damages derived from the materialization of occupational accidents entail a series of problems at a personal, family and social level that generate a negative impact on the environment. In this sense, the objective is to investigate the evolution of occupational accident rates by geographical zones of Ecuador, using the database of the Ecuadorian Institute of Social Security and identifying the associated variables during the period from 2015 to 2021. Through a comparative and correlational statistical analysis of the qualified accidents according to the study variables, it was possible to determine that the geographical areas of Ecuador with the highest occupational accident rate are zones 5 and 2 (73%), where there are also the highest number of qualified accidents from manufacturing industries (23.72%), occurring in the workplace (63%). The sex that presents the greatest number of qualified accidents is male and the parts of the body that suffer the greatest injury are the upper limbs (35%). Finally, it is concluded that in order to improve occupational safety in organizations, it is necessary a commitment between the state, employers and workers, key actors for the generation of a culture of prevention based on various strategies.